ANALISIS TINGKAT KEBUGARAN JASMANI SISWA KELAS VI DI SD BAITU ILMIN SURABAYA - Nanda Alifia; Sunanto; Sri Hartatik; Dewi Widiyana Rahayu (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This research aims to analyze the physical fitness level of sixth-grade students at SD Baitul Ilmin Surabaya using the Indonesian Student Fitness Test (TKSI) Phase C instrument. Physical fitness is a crucial aspect in supporting optimal growth and academic readiness. The research method employed was descriptive quantitative with a survey approach, involving all 18 sixth-grade students as a total sampling. Data were obtained through direct measurement of the five TKSI Phase C test items. The results indicate that the students' physical fitness level is dominated by the Moderate category (50.00%). There is an equal proportion in the Good (22.22%) and Less (22.22%) categories, while 5.56% of students fall into the Very Less category, and 0% in the Very Good category. These findings suggest that the students' fitness profiles are not yet optimal and require special attention. It is recommended that schools and physical education teachers implement sustainable physical intervention programs to improve students' physical fitness to support their health and learning quality.